Arthritis and arthralgia as an adverse event following immunization: A systematic literature review. Issue 2 (7th January 2019) - Panozzo, Catherine A.; Pourmalek, Farshad; Brauchli Pernus, Yolanda; Pileggi, Gecilmara S.; Woerner, Andreas; Bonhoeffer, Jan; ,
Abstract: Background: Arthritis and arthralgia are reported as adverse events following immunization with various vaccines. Objective: To better understand current knowledge of arthritis and arthralgia as an adverse event following immunization. Methods: A systematic literature review of Pubmed, Embase, and Cochrane Library was conducted. Data extraction was performed by two independent reviewers. No restrictions on dates were imposed and all types of vaccine studies with primary data were reviewed. Results: Of 343 included studies, there were 206 clinical trials, 90 observational studies, and 47 case reports. Influenza was the most commonly studied vaccine (n = 91, 24.4%). Of the 155 (45.2%) studies addressing causality assessment, 84 studies (54.2%) revealed the assessment method. Only seven clinical trials and 12 observational studies reported a measure of association. Four of these studies examined worsening of arthritic conditions in patients with pre-existing disease. Rigorous assessment of causality was not performed in most studies and many observational studies were prone to bias. Conclusions: The current evidence linking vaccination to incident arthritis or worsening of arthritic conditions is too heterogeneous and incomplete to infer a causal association. Recommendations for future studies include use of consistent, standardized case definitions and causality assessments, better control of confounding and minimization of bias, and inclusion of measures of associations.